SISTEM PERADILAN ISLAM DI BAWAH WILAYAT AL-FAQIH: KAJIAN KOMPARATIF ANTARA IRAN DAN INDONESIA - Ulfa, Rusda; Asasriwarni, Asasriwarni; Zulfan, Zulfan (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study examines the influence of the Wilayat al-Faqih principle on the Islamic judiciary system in the Islamic Republic of Iran and compares it to the religious court system in Indonesia. The focus is on how Shia Imamiyyah doctrine shapes Iran's legal and judicial structures, including the Supreme Court and Revolutionary Courts, highlighting the strong interplay between religion and politics. Conversely, Indonesia separates religious authority from the state, with its religious courts under the Supreme Court and free from political ideologies. A qualitative descriptive method, based on primary and secondary sources, was employed. The findings reveal that Wilayat al-Faqih grants extensive power to the Supreme Leader over Iran's judiciary, unlike Indonesia's pluralistic legal system. In family law, Iran adopts Shia-based practices, such as mut’ah marriage and lower marriageable ages, while Indonesia has reformed family law to establish higher minimum marriage ages. In conclusion, religious ideology profoundly influences Iran's legal policies, whereas Indonesia offers a more inclusive and pluralistic legal framework.